(untitled) (Annals of Medical Research, 2024)
Aim: This study aimed to assess the rates of peer bullying and stress-coping strategies in adolescents with SAD and to investigate the relationship between SAD and different types of peer bullying. Materials and Methods: This cross-sectional study included ninety-two adolescents aged 14 to 17 years with SAD and one hundred-five typically developing adolescents. A semi-structured psychiatric interview, the Social Anxiety Scale for Adolescents (SAS-A), the Peer Bullying Scale-Adolescent Form (PBS-AF), and the Coping Scale for Adolescents (CSA) were applied to all participants. Peer bullying was classified into six types (physical, verbal, exclusion, spreading rumors, attacks against property, and sexual) and two roles (bullying and victimization). Results: On every subscale of the PBS-AF victimization dimension, the SAD group’s mean scores were significantly higher than those of the controls. Regarding the PBS-AF bullying dimension, the Physical Bullying and Sexual Bullying scores of the SAD group were significantly lower than the control group, but the Isolation/ Exclusion scores were significantly higher than the control group. Compared to the control group, the mean scores of Active Coping of CSA were significantly lower, while the mean scores of Negative Coping and Avoidant Coping were significantly higher in the SAD group. The SAS-A’s total score had a significant positive correlation with all subscales of the PBS-AF victimization dimension. Age, gender, academic performance, and psychiatric comorbidity had a predictive effect on some of the victimization dimension variables of peer bullying. Conclusion: This study has revealed that SAD is an important risk factor for peer victimization. The routine psychiatric examination of adolescents with SAD should also include a screening for peer bullying.